PRPF19 modulates morphology and growth behavior in a cell culture model of human skin - Kleissl, Lisa; Weinmüllner, Regina; Lämmermann, Ingo; Dingelmaier-Hovorka, Ruth; Jafarmadar, Mohammad; El Ghalbzouri, Abdoelwaheb; Stary, Georg; Grillari, Johannes; Dellago, Hanna (Frontiers in Aging, 2023)
The skin provides one of the most visual aging transformations in humans, and premature aging as a consequence of oxidative stress and DNA damage is a frequently seen effect. Cells of the human skin are continuously exposed to endogenous and exogenous DNA damaging factors, which can cause DNA damage in all phases of the cell cycle. Increased levels of DNA damage and/or defective DNA repair can, therefore, accelerate the aging process and/or lead to age-related diseases like cancer. It is not yet clear if enhanced activity of DNA repair factors could increase the life or health span of human skin cells. In previous studies, we identified and characterized the human senescence evasion factor (SNEV)/pre-mRNA-processing factor (PRPF) 19 as a multitalented protein involved in mRNA splicing, DNA repair pathways and lifespan regulation. Here, we show that overexpression of PRPF19 in human dermal fibroblasts leads to a morphological change, reminiscent of juvenile, papillary fibroblasts, despite simultaneous expression of senescence markers. Moreover, conditioned media of this subpopulation showed a positive effect on keratinocyte repopulation of wounded areas. Taken together, these findings indicate that PRPF19 promotes cell viability and slows down the aging process in human skin.